The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1242/dmm.043281
|View full text |Cite
|
Sign up to set email alerts
|

Absence of p.R50X Pygm read-through in McArdle disease cellular models

Abstract: McArdle disease is an autosomal recessive disorder caused by the absence of muscle glycogen phosphorylase, which leads to blocked muscle glycogen breakdown. We used three different cellular models to evaluate the efficiency of different read-through agents (including amlexanox, Ataluren, RTC13 and G418) in McArdle disease. The first model consisted of HeLa cells transfected with two different GFP-PYGM constructs presenting the Pygm p.R50X mutation (GFP-PYGM p.R50X and PYGM Ex1-GFP p.R50X). The second cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Adenine is most preferred in the 5’ position for highest readthrough whereas cytosine is 3-6 times more effective in the 3’ position such as UGA-C in all TRID studies even though the optimal subsequent order of bases is TRID-dependent [84] , [85] , [86] , [87] . Interestingly, the base immediately following the stop codon exerts the strongest influence on readthrough efficiency due to the interaction of mRNA with release factors to terminate translation [ 84 , 88 ]. Computer modelling has suggested PTC124 has a preference for UGA readthrough due to a more favourable binding energy than UAG or UAA stop codons [89] .…”
Section: Discussionmentioning
confidence: 99%
“…Adenine is most preferred in the 5’ position for highest readthrough whereas cytosine is 3-6 times more effective in the 3’ position such as UGA-C in all TRID studies even though the optimal subsequent order of bases is TRID-dependent [84] , [85] , [86] , [87] . Interestingly, the base immediately following the stop codon exerts the strongest influence on readthrough efficiency due to the interaction of mRNA with release factors to terminate translation [ 84 , 88 ]. Computer modelling has suggested PTC124 has a preference for UGA readthrough due to a more favourable binding energy than UAG or UAA stop codons [89] .…”
Section: Discussionmentioning
confidence: 99%
“…With regard to gene therapy, although encouraging, positive results have been reported with the ovine and mouse model [ 74 , 75 ], more studies are still needed in order to induce actual increases in the expression of the transgene in the skeletal muscle to further reverse the clinical phenotype before this approach can be proposed for patients. Finally, RTA agents have also been evaluated in vitro both in transiently transfected cells and in skeletal muscle cultures derived from the McArdle mouse model, and the absence of read-through induction with the different tested compounds [ 73 , 91 ], has prevented further studies using in vivo models. This being said, because the number of potential RTA is constantly increasing, it cannot be completely ruled out that a new RTA might be useful for the treatment of McArdle disease.…”
Section: Critical Discussionmentioning
confidence: 99%
“…Seven years later, RTA were again evaluated as potential therapeutic compounds for McArdle disease, and this time read-through activity was observed in non-muscle cell cultures transiently transfected with p.R50X-green fluorescent protein (GFP) constructs when treated with an aminoglycoside antibiotic, G418 [ 85 ]. Recently, in order to further clarify the potential benefit of these compounds as therapeutic agents, a wider battery of RTAs (including amlexanox, Ataluren, RTC13, RTC14 and G418, among others) were tested again in transiently transfected cells with p.R50*-GFP but also in cells stably expressing these constructs and in skeletal muscle cultures derived from the McArdle mouse model [ 73 ]. In this study, no read-through induction was observed in any of the cells with the different RTA tested.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different RTAs were tested in different McArdle disease cell cultures models: (1) transiently transfected cells with p.R50X plasmid constructs, (2) cells stably expressing p.R50X plasmid constructs and (3) skeletal muscle cells derived from the Pygm R50X/R50X mouse model. Even though it was a promising therapy, no read-through induction was observed in any of these cells cultures with any of the RTAs tested, but further studies are needed to provide a better understanding of these drugs [ 241 ].…”
Section: Glycogen Storage Diseasesmentioning
confidence: 99%